Creative Thinking in Mathematics - Tri Cahya Mulia; Wardani Rahayu (Prima: Jurnal Pendidikan Matematika, 2023)
Creative thinking is important in increasing the formation and discovery of learning ideas in the 21st century. The 21st century is closely related to the era of the industrial revolution 4.0 which requires humans to have the ability to think more creatively and be able to accept rapid technological developments. Through education and learning, the ability to think creatively can be improved for the better. The ability to think creatively which is one of the cognitive abilities in learning activities needs to be developed. When the ability to think creatively develops, it will give birth to ideas, find interrelated relationships, create and carry out imaginations, and have many perspectives on things. Students who have high creative thinking skills tend to feel challenged and interested in solving various problems in learning. Interest in solving this problem also causes curiosity. A student with mathematical creative thinking has the ability to be able to solve problems he encounters in new or unusual ways. The tendency of mathematics teachers to dominate learning results in low student activity so that they do not provide opportunities to be directly involved in scientific activities. These conditions have an impact on students' limited opportunities to think creatively in finding new information or ideas from the learning process, it is necessary to increase creative thinking in learning which can be done in various ways.